Factors affecting the net profit margin and the financial ratios of selected universal banks - Cataylo, Francheska Ann T., Jadolos, Catherine Anne C., Ladignon, Estephanie Gaebrielle M., Lopez, John Louie., Rodriguez, Nicole. 4 0 16; 5
Abstract Universal banks play a pivotal role in the financial ecosystem by offering a wide range of services, including deposit-taking, lending, and investment banking, under one roof. To navigate the complexities of the banking sector, financial indicators serve as crucial tools for assessing performance and making informed decisions. This study investigates the correlation between various financial ratios and net profit margin in selected universal banks from 2019 to 2023. Understanding these correlations is paramount for evaluating the financial health and profitability of banks, as they provide insights into how different aspects of a bank's operations impact its bottom line. Financial indicators such as liquidity, solvency, efficiency, and profitability are crucial for the net profit margin of universal banks. These indicators assess the bank's financial health, operational efficiency, and ability to generate profits. Liquidity ratios ensure the bank can meet short-term obligations, while solvency ratios indicate long-term stability. Efficiency ratios identify areas for improvement, optimizing operations for higher profitability. Strong financial indicators attract investor confidence, driving capital influx. Overall, these indicators guide strategic decisions, mitigate risks, and influence the net profit margin of universal banks. Specifically, the study focuses on determining the relationships between liquidity, solvency, efficiency, and profitability ratios and their influence on net profit margin. The lack of related literature in this area underscores the novelty and importance of this research, as it fills a gap in understanding the financial dynamics of universal banks. Targeted at financial managers, analysts, and auditors in the banking industry, this study aims to provide valuable insights and benchmarks for assessing financial performance and guiding strategic decision-making. By establishing correlations between key financial metrics and net profit margin, the study equips stakeholders with the tools needed to optimize operational efficiency and enhance profitability. The findings of this study hold significant implications for the economy and universal banks. By providing a deeper understanding of the factors driving profitability in the banking sector, the research contributes to overall financial stability and growth. Moreover, it empowers banks to adapt their strategies in response to changing market conditions, thereby fostering a more resilient and competitive banking industry.
Research Paper: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2